Furthering the potential of apatite as a provenance indicator in sedimentary systems - O'SULLIVAN, GARY JOHN (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2019)
As a mineral that has only recently become possible to date routinely by the U-Pb method, apatite geochemistry (U-Pb isotopes and trace elements) has until now attracted less attention than longer-established detrital chronometers such as zircon. This has resulted in a mismatch between the potential of apatite as a detrital geochronometer and our understanding of what the geo- or thermo-chronological information that it contains means, and how its trace-element geochemistry relates to source lithology. This thesis investigates U-Pb age data from apatite and other chronometers in detrital systems to provide insight into the different age-information that is recorded by apatite compared to other mineral chronometers, with apatite proving particularly effective at recording magma-poor orogenesis and recording more recent geological events in its source area than other chronometers. This thesis also examines apatite trace-element compositions and their potential for use alongside U-Pb ages in detritus. While apatite trace-element compositions have previously been investigated in provenance studies (though never in combination with U-Pb ages), the choice of elemental ratios employed has led to poor separation on discrimination plots resulting in only generalised provenance determinations being possible. In this PhD a different approach has been taken, whereby a large database of apatite bedrock compositions was assembled and visualised using principal component analysis to create an empirical apatite discriminant diagram against which unknown detritus can be plotted. Using this methodology full separation of many lithological classes of apatite is possible (low- to medium-grade metamorphic, high-grade metamorphic, S-type granitoids, ?felsic? Itype granitoids, ?mafic? I-type granitoids and basic igneous rocks, alkaline igneous rocks, adakites, ultrabasic igneous rocks, and authigenic apatite). Given that it is now possible to couple the U-Pb ages and source lithology of detrital apatite reliably using the methodology developed here, this opens the door to highly specific provenance determinations. The detrital case studies presented in this thesis demonstrate that novel insights can be gained from these data, including new information on the generation of sandstones, the history of denudation of the earth?s surface, and the evolution of drainage networks and the tectonic forces that created them.
APPROVED
Keywords: Detrital geochronometers; Apatite geochemistry